Testing the phylogenetic position of Cambrian pancrustacean larval fossils by coding ontogenetic stages. (27th August 2013) - Wolfe, Joanna M.; Hegna, Thomas A.
Abstract The study of ontogeny as an integral part of understanding the pattern of evolution dates back over 200 years, but only recently have ontogenetic data been explicitly incorporated into phylogenetic analyses. Pancrustaceans undergo radical ontogenetic changes. The spectacular upper Cambrian "Orsten" fauna preserves phosphatized fossil larvae, including putative crown‐group pancrustaceans with amazingly complete developmental sequences. The putative presence and nature of adult stages remains a source of debate, causing spurious placements in a traditional morphological analysis. We introduce a new coding method where each semaphoront (discrete larval or adult stage) is considered an operational taxonomic unit. This avoids a priori assumptions of heterochrony. Characters and their states are defined to identify changes in morphology throughout ontogeny. Phylogenetic analyses of semaphoronts produced possible relationships of each Orsten fossil to the crown‐group clade expected from morphology shared with extant larvae. Bredocaris is a member of the stem lineage of Thecostraca or (Thecostraca + Copepoda), and Yicaris and Rehbachiella are probably members of the stem lineage of Cephalocarida. These placements rely directly on comparisons between extant and fossil larval character states. The position of Phosphatocopina remains unresolved. This method may have broader applications to other phylogenetic problems which may rely on ontogenetically variable homology statements.